Pengaruh Dana Syirkah Temporer Terhadap Profitabilitas Dengan Risiko Pembiayaan Sebagai Variabel Intervening - Nurul Syahla (Jurnal Ilmiah Ekonomi Islam, 2023)
This study aims to determine the impact on the profitability of the Temporary Syirkah Fund in PT Bank Sumut Unit Usaha Syariah for the period 2017-2021 with funding risk as an intervening variable. In general, an increase in Temporary Syirkah Funds increases the return on investment and reduces funding risk. However, there are discrepancies with the presented theory due to the data obtained. Data are presented through normality and path analysis tests to analyze relationships between variables. The results of this study showed a significance test of 0.524 for the impact of temporary cirka funds on profitability. The significance test for the effect of Temporary Syirkah Funds on funding risk was 0.928. Both are more than 5% significant, meaning there is no significant effect on either variable. The direct effect value is higher than the indirect effect, indicating that the Syirkah Fund does not have a significant impact on direct funding risk through profitability. Based on the R-squared value, the variable's contribution to the funding risk of Temporary Syirkah Funds and Profitability is 0.9%. In contrast, the remaining 99.1% are contributed by other variables not included in the study.